Computer crime and security a survey of financial institutions in Malaysia - Salim, Basariah; Tayib, Mahamad; Abidin, Shamharir (Universiti Utara Malaysia, 2002)
Studies in United States of America, Europe and Australia show that computer crime has grown along with the increase in the use of computers. In our survey, we found that computer crime also happened in Malaysian financial institutions, which reported around 22.86% out of 116 effectively surveyed respondents. In general, the result of this study showed that financial institutions in Malaysia are not seriously threatened by computer crime as compared to those countries. Moreover, they are also aware and have taken several steps regarding securities policy and procedure of their systems.